Replication of B19 parvovirus in highly enriched hematopoietic progenitor cells from normal human bone marrow. - Srivastava, A (1988)
The target cell specificity of the B19 parvovirus infection was examined by isolating highly enriched hematopoietic progenitor and stem cells from normal human bone marrow. The efficiency of the B19 parvovirus replication in enriched erythroid progenitor cells was approximately 100-fold greater than that in unseparated bone marrow cells. The more-primitive progenitor cells identical to or closely related to the human pluripotent hematopoietic stem cells, on the other hand, did not support viral replication. The B19 progeny virus produced by the enriched erythroid progenitor cells was infectious and strongly suppressed erythropoiesis in vitro. The susceptibility of both the more-primitive erythroid progenitors (burst-forming units-erythroid) and the more-mature erythroid progenitors (CFU-erythroid) to the cytolytic response of the virus and the lack of effect on the myeloid progenitors (CFU-granulocyte-macrophage) further give evidence to the remarkable tropism of the B19 parvovirus for human hematopoietic cells of erythroid lineage.